2020
DOI: 10.1002/leg3.57
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, textual, and archeological evidence of the historical global spread of cowpea (Vigna unguiculata[L.] Walp.)

Abstract: Cowpea (Vigna unguiculata [L.] Walp.) was originally domesticated in sub‐Saharan Africa but is now cultivated on every continent except Antarctica. Utilizing archeological, textual, and genetic resources, the spread of cultivated cowpea has been reconstructed. Cowpea was domesticated in Africa, likely in both West and East Africa, before 2500 BCE and by 400 BCE was long established in all the modern major production regions of the Old World, including sub‐Saharan Africa, the Mediterranean Basin, India, and Sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 36 publications
5
48
0
1
Order By: Relevance
“…Landraces and their breeding derivatives from California belong to Subpopulation 3, which is composed mostly of landraces from Mediterranean countries, while accessions from other U.S. states were predominantly from Subpopulation 6, which is composed mostly of landraces from Southeastern Africa. This population structure, together with textual evidence summarized by Herniter et al [40], is consistent with a global dispersal of cowpea from its centers of domestication in West and East Africa along historical trade routes. For the USA, cowpea appears to have arrived through at least two distinct introduction routes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Landraces and their breeding derivatives from California belong to Subpopulation 3, which is composed mostly of landraces from Mediterranean countries, while accessions from other U.S. states were predominantly from Subpopulation 6, which is composed mostly of landraces from Southeastern Africa. This population structure, together with textual evidence summarized by Herniter et al [40], is consistent with a global dispersal of cowpea from its centers of domestication in West and East Africa along historical trade routes. For the USA, cowpea appears to have arrived through at least two distinct introduction routes.…”
Section: Discussionsupporting
confidence: 85%
“…Although the germplasm utilized in this study largely overlaps with that utilized by Huynh et al [10], only two genetic clusters were identified in that previous study which correspond to the two major "West Africa" and "Southeastern Africa" gene pools. As shown by Herniter et al [40] utilizing this same UCR Minicore material, at K=2 Subpopulation 6 (Southeastern Africa gene pool) splits from the rest of the subpopulations, confirming that as a primary genetic differentiation between subpopulations of domesticated cowpeas. The smaller number of SNPs that were available for Huynh et al [10] to conduct population structure analyses, together with an emphasis on African landraces among accessions genotyped, most likely precluded further subdivision of the West African subpopulation.…”
Section: Population Structure and Historical Crop Dispersalsupporting
confidence: 67%
See 2 more Smart Citations
“…Five of the six subpopulations were composed mostly of landraces, while Subpopulation 2 included cowpea lines only from IITA's cowpea breeding program. Based on how the six subpopulations split at different K numbers, as illustrated in Herniter et al (2020), it appears that Subpopulation 2 is the result of crosses between materials from Subpopulations 1 and 5. Subpopulations 1 and 5 are composed almost exclusively of West African accessions.…”
Section: Discussionmentioning
confidence: 99%